Association between the site of clear corneal Phakic intraocular lens implantation incisions and the inflow of ocular surface fluid into the anterior chamber - Wan, Huan; Tao, Yunhan; Duan, Jianan; Wang, Lin; Tang, Li (Frontiers in Medicine, 2023)
Background: Posterior chamber phakic intraocular implantable collamer lens (ICL) implantation is an effective surgical option for the management of myopia. Over the past few years, the number of ICL surgeries has significantly increased. Postoperative inflammation and endophthalmitis are among the most serious complications after successful ICL surgery. Sometimes, when the blepharospasm is removed at the end of surgery, a small amount of the ocular surface fluid will flow into the anterior chamber, which can lead to an increased risk of infection and inflammation. However, little attention has been paid to this phenomenon. Purpose: We conducted a retrospective study to compare the incidence of extraocular fluid inflow into the eye through the clear corneal incision (CCI) at two different positions (superior and temporal sides). Methods: A total of 116 patients with myopia underwent superior CCI ICL implantation (n=58) or temporal CCI ICL implantation (n=58) at our hospital from October to December 2021. The incidence of conjunctival sac fluid entering the anterior chamber after eyelid fixative was removed was compared in both groups. Results: Both groups were well matched in all parameters. Ocular surface fluid inflow into the anterior chamber was significantly higher in the superior CCI group (25/58, 47.1%) than in the temporal CCI group (1/58, 1.7%) (P<0.05). Conclusions: In the patients with ICL implantation, the temporal CCI was better than the superior CCI in avoiding the ocular surface fluid inflow into the anterior chamber, and the potential risk of infection and inflammation was lower.